Hagar and Ishmael: A Commentary. (July 2014) - Cohen, Aryeh
This essay offers a commentary on the short story of Hagar and Ishmael's expulsion at the hands of Abraham (Gen 21:14–20). The commentary lays a claim on traditional interpretation but is not itself necessarily a traditional interpretation.